2007
DOI: 10.1103/physrevlett.99.176401
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Van Der Waals Interaction for Organic Molecule-Metal Junctions: Adsorption of Thiophene on Cu(110) as a Prototype

Abstract: We report ab initio calculations for the interface energetics of a weakly adsorbed organic molecule on a metal surface, which serves as a model interface relevant for organic electronics. The studied thiophene ring is found to be physisorbed on the Cu(110) surface with an adsorption energy of -0.50 eV. Nonlocal correlations, i.e., van der Waals interactions, are solely responsible for the binding in this weakly interacting system, and the choice of the proper exchange-correlation function is crucially importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
164
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(174 citation statements)
references
References 35 publications
9
164
0
1
Order By: Relevance
“…Previous theoretical and experimental studies showed that dispersive forces play a crucial role in this system, just as in the adsorption of aromatic molecules on metal surfaces [15,17,18].…”
Section: Introductionmentioning
confidence: 89%
“…Previous theoretical and experimental studies showed that dispersive forces play a crucial role in this system, just as in the adsorption of aromatic molecules on metal surfaces [15,17,18].…”
Section: Introductionmentioning
confidence: 89%
“…For adsorption of molecules on metal surfaces, the inclusion of van der Waals interactions has been shown to be important to predict adsorption energies and geometries [39][40][41][42][43] , especially for Alq 3 molecule adsorption on metals 23,25 . A review of techniques for computing van der Waals interactions in density functional theory is given in Ref.…”
Section: Methods Of Calculationmentioning
confidence: 99%
“…15 These work functions can then be additionally tuned by noncovalent adsorption of organic molecules on the metallic surface in hybrid organic−inorganic interfaces. 15,303,316 …”
Section: Structural and Electronic Propertiesmentioning
confidence: 99%